Tourism Marketing Strategy of Legenda Tapaktuan Tourist Attraction in South Aceh District, Aceh Province - Anismar Anismar; Iskandar Zulkarnain; Syukur Kholil; Suswanta Suswanta (Journal of Governance and Public Policy, 2023)
This study aims to identify and produce a relational marketing strategy for the Legend of Tapaktuan tourist attraction. This research used relational theory and emphasized partnership and collaboration with the aim of a sustainable tourism program. Indicators in related programs can relate to the relationship between various parties involved in the tourism industry. The problem formulation in this study is the ideal marketing strategy for the Legend of Tapaktuan tourist attraction in Aceh Province. This study used a descriptive method with a qualitative approach. The results showed that the South Aceh District Tourism Office has tried to promote not only through out-of-town trips but also through online media. To make the Tapaktuan Legend tourist attraction more advanced, the South Aceh District Government carried out the first promotion strategy, advertising and promoting Tour & Travel Online services on a number of social media platforms such as Instagram, Facebook and Twitter. The government also offers a number of tour packages by participating in expo activities outside the region to introduce and re-promote tourist destinations, especially the Tapaktuan Legend tourist attraction as an icon of South Aceh. Tourists only need to download an application that provides many features that can be used, such as directions, maps, lodging, and how to get to the location. This application also provides a transportation feature that will make it easier for tourists to visit tourist sites.